Gentamycin injection in disc space during lumbar discectomy (aiming to prevent post - operative discitis) - AbdulWahid, Ali T. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Postoperative discitis is uncommon 4%, but it is the most disabling postoperative complication after lumbar discectomy.Objective: To assess the effectiveness of intradiscal Gentamycin in prevention of lumbar discitis post operatively.Patients and Methods: This is a prospective study involving 320 patients, who had lumbar discectomy. 140 patients (first group) from Jan. 2012 to Jan. 2013 were not had intradiscal gentamycin injection, while 180 patients (2nd group) From Jan 2013 to Jan 2014 (2nd group) had intradiscal injection of 80mg Gentamycin at the end of surgery and before closing up. Follow up was done 10 days to 6weeks after surgery by W.B.C count, ESR, C-reactive protein and clinical assessment.Results: There were eight cases (6%) of postoperative discitis in the first group, while in the second group there was only one patient (0.5%) with postoperative discitis who had intradiscal injection of Gentamycin (0.5%).Conclusions: Intradiscal Gentamycin injection during lumbar discectomy is effective in preventing of postoperative discitis.